Doll Claw Machine Phenomenon in Rural Areas: A Review of Gharar Transactions, Socio-Economic Implications, and Compliance with Islamic Economic Principles - Luntajo, Mohammad Muzwir Rusliansyah; Mamonto, Meisi; Hasan, Faradila; Blazhevich, Yuliya S. (IAIN Manado, 2024)
Doll claw machine games have become an increasingly popular phenomenon in Indonesia, including in Poyowa Besar Village, Kotamobagu. Although appearing as entertainment, the presence of doll claw machines raises concerns from an Islamic economic perspective due to containing elements of gharar. This research aims to evaluate the practice of doll claw machine games from an Islamic economic perspective, focusing on three aspects: review of gharar transactions, socio-economic implications, and compliance with Islamic economic principles. Using a qualitative approach with case study methods, this research conducted semi-structured interviews with shop owners and parents, participatory observation, and document study. The results show that doll claw machine games contain significant gharar elements in their transaction procedures and business model. The identified socio-economic implications include increased family expenditure burden, changes in children's consumption patterns, and addiction risks. From an Islamic economic perspective, this practice contradicts fundamental principles such as the prohibition of gharar and protection of wealth (hifz al-mal). In conclusion, doll claw machine games in Poyowa Besar Village require re-evaluation and stricter regulation to protect the community from economic practices that do not comply with sharia.